2022
DOI: 10.1021/acs.joc.2c01545
|View full text |Cite
|
Sign up to set email alerts
|

Hydride Relay Exchange Mechanism for the Heterocyclic C–H Arylation of Benzofuran and Benzothiophene Catalyzed by Pd Complexes

Abstract: The mechanism and regioselectivity of the heterocyclic C–H arylation of benzofuran and benzothiophene catalyzed by Pd­(OAc)2 complexes were investigated using the density functional theory (DFT) method. The Pd(0)­L2(PhI) complex (L = HOAc) is proposed to be the catalytic species. Compared to the traditional Heck-type mechanism, concerted metalation-deprotonation (CMD) mechanism, and electrophilic aromatic substitution (SEAr) mechanism for the C–H arylation, a new hydride relay exchange mechanism was proposed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 88 publications
1
4
0
Order By: Relevance
“…63,64,68,74−78 Furthermore, a kinetic isotope effect (KIE) study was conducted, and the small magnitude of KIE (1.17) showed that the cleavage of the C−H bond is unlikely to be involved in the rate-determining step (Scheme 3-iii). 63,64,68,74−78 Beyond the CMD mechanism, an S E Ar mechanism at the C-2 site of benzofuran followed by reductive elimination and rearomatization 58,74,79,80 or an electrophilic attack of cationic palladium followed by aryl ligand migration 78 seem more likely to be responsible for the reaction, which is consistent with the results of deuterium scrambling and the KIE studies. In addition, the Heck-type mechanism might also be possible, as demonstrated by many others.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…63,64,68,74−78 Furthermore, a kinetic isotope effect (KIE) study was conducted, and the small magnitude of KIE (1.17) showed that the cleavage of the C−H bond is unlikely to be involved in the rate-determining step (Scheme 3-iii). 63,64,68,74−78 Beyond the CMD mechanism, an S E Ar mechanism at the C-2 site of benzofuran followed by reductive elimination and rearomatization 58,74,79,80 or an electrophilic attack of cationic palladium followed by aryl ligand migration 78 seem more likely to be responsible for the reaction, which is consistent with the results of deuterium scrambling and the KIE studies. In addition, the Heck-type mechanism might also be possible, as demonstrated by many others.…”
Section: Resultssupporting
confidence: 58%
“…In addition, the Heck-type mechanism might also be possible, as demonstrated by many others. 57,59,60,63,64,68,74 Finally, although we cannot rule out the possibility of the Pd 3 cluster acting as a reservoir to in situ generate some mononuclear Pd species or nanoparticles, the ultraviolet−visible (UV−vis) spectra of the solution in the reaction process (Scheme 3-iv) showed that the Pd 3 Cl absorption spectrum remained essentially unchanged over the reaction course, 31 indicating that the Pd 3 cluster core might not undergo substantial change or decomposition during catalysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transition metal catalysts are widely used in organic synthesis. To evaluate the efficacy of the i-EIP method for transition metal-catalyzed reactions, five reactions were selected from a variety of published libraries for use as a test set. The selected reactions contain different transition metal atoms, and the size of these reaction systems is relatively large.…”
Section: Resultsmentioning
confidence: 99%